2021
DOI: 10.3389/fmicb.2021.692147
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hepatitis E Virus in Hyalomma lusitanicum Ticks Feeding on Wild Boars

Abstract: Little is known about the role of ticks in maintaining highly prevalent zoonotic viruses in wildlife, such as hepatitis E virus (HEV), which do not require ticks for transmission between animals and humans. In this cross-sectional study, adult female ticks were collected from Eurasian wild boar (Sus scrofa) in autumn 2015 in Spain. HEV RNA in both ticks and wild boar was evaluated by RT-qPCR. Twenty-nine adult Hyalomma lusitanicum ticks were collected from 29 wild boars. HEV RNA was detected in a total of 10 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The infection predominantly affects middle-aged or elderly males and is characterized by a higher frequency of non-specific symptoms [ 7 ], such as neurological symptoms and disorders, hematological disorders, renal disease, acute pancreatitis, myocarditis, arthritis, and autoimmune thyroiditis [ 8 ]. In addition to animal reservoirs, HEV genotype 3 has been isolated from various environmental matrices, such as contaminated surface water [ 9 ], wastewater treatment plants [ 10 ], and even ticks [ 11 ]. Chronic HEV infection, which is typical for genotype 3 and rare for genotype 4, has been reported in immunocompromised patients, such as solid organ transplant patients, HIV-infected, or patients with hematologic malignancies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The infection predominantly affects middle-aged or elderly males and is characterized by a higher frequency of non-specific symptoms [ 7 ], such as neurological symptoms and disorders, hematological disorders, renal disease, acute pancreatitis, myocarditis, arthritis, and autoimmune thyroiditis [ 8 ]. In addition to animal reservoirs, HEV genotype 3 has been isolated from various environmental matrices, such as contaminated surface water [ 9 ], wastewater treatment plants [ 10 ], and even ticks [ 11 ]. Chronic HEV infection, which is typical for genotype 3 and rare for genotype 4, has been reported in immunocompromised patients, such as solid organ transplant patients, HIV-infected, or patients with hematologic malignancies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though HEV has a wide host range and is maintained efficiently by wild ungulates ( 7 , 9 ), only two studies have evaluated the presence of the virus in arthropods. In a previous study, we found that ticks ( Hyalomma lusitanicum ) that had fed on viremic animals were positive for HEV, although it was not possible to demonstrate the vectorial capacity of these arthropods ( 13 ). In another study, Vandeweyer et al ( 40 ) assessed the risk of transmission of certain foodborne pathogens by eating insects and did not find HEV RNA in 92 crickets ( Acheta domesticus ) analyzed.…”
Section: Resultsmentioning
confidence: 95%
“…A plausible hypothesis is the involvement of an arthropod vector with high spring-summer activity ( 11 , 12 ). Two main arthropod vectors, ticks, previously suggested by our group ( 13 ), and mosquitoes, which have not yet been evaluated, could be linked to HEV maintenance and transmission due to their intimate ecological association with the wild ungulates that maintain zoonotic HEV genotypes, as well as their wide distribution, and abundance ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study evidenced that liver transudate could be used for HEV RNA detection (Navarro et al, 2020 ). A study reported HEV RNA in 27.9% (11/29) of Hyalomma lusitanicum ticks feeding on wild boars and in 34.5% (10/29) of wild boar serum samples, further typing as HEV-3 subgenotype 3f (Antonio Rivero-Juarez et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%